Building ISO 9000 based quality management systems in education : the case of the Faculty of Business Management, UiTM Shah Alam / Norhana Salamudin, Noraini Ismail and Hazman Shah Abdullah - Salamudin, Norhana; Ismail, Noraini; Abdullah, Hazman Shah (Institute of Research, Development and Commercialization (IRDC), 2005)
This study examines a managerial innovation involving developing, implementing and accrediting a quality management system based on the ISO 9000 international standard. There is moderate correlation between interest in managerial innovation and perceived value. Implementation strategy/approach shows a relatively high correlation with perceived value. Staff reaction to innovation is connected to their interest and perceived value towards personal and institutional development, and growth. The multiple regression analysis shows that the model explains /5% to 19% ofthe variance in innovation acceptance with interest being the only significant variable. The moderating role of implementation prior to the exercise was examined via the hierarchical regression analysis. The results indicate that implementation strategy interacts with the interest variable enhancing the explanatory power to 24%. The resulting Rl change adds weight to the claim that the implementation strategy plays a critical role in generating acceptance ofthe innovation introduced A more inclusive and participative strategy is likely to generate greater interest and engagement and induce greater acceptance ofthe innovation. Thus, any implementation strategy that does not incorporate involvement, consultation and consensus building among members will deepen existing chasm between managers and the managed Nowhere is this chasm more visible than in the academia.